Instituições participativas e instituições representativas : convergência de agendas e encontros efetivos - Souza, Valéria Cristina Dadalto Pimenta de (2016)
This current dissertation dialogued with the latest studies on Participatory Institutions, aiming to analyze whether there was convergence between the agendas of Participatory Institutions and Representative Institutions. Secondly, it is aimed to find out whether this convergence was the result of effective meetings or not. The Participatory institutions were represented by the 10th Health State Conference of Paraná and Representative Institutions by the State Legislative Assembly. The work addressed the theoretical conceptualization of Participatory Institutions with emphasis on Public Policy Conference. To analyze this convergence, they were studied the deliberations of the 10th Health State Conference which required treatment of the legislative power and the bills relating to public health in the period from 2011 to 2014. The survey revealed that there is convergence between the agendas of Participatory Institutions and Representative Institutions, therefore, it found that this convergence is not the result of effective meetings. It is sought to identify ways which could contribute to that soon the effectiveness of meetings is achieved because it is need special attention of researchers to Participatory Institutions necessity are also looked outside of it. It is become extremely important to know whether their products reach and transform the public policy positively surrounding of which the Participatory Institutions were built.